2004
DOI: 10.1520/jte10861
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hot Mix Asphalt Macro- and Microtexture

Abstract: Pavement macrotexture is considered the primary factor in skid resistance at speeds over 65 km/h (40 mph). A total of 18 projects (9 Superpave and 9 Marshall mix designs) were evaluated to determine if the macrotexture of the pavement surface was influenced by gradation changes associated with the move to Superpave mix designs. The Federal Highway Administration ROSAN high-frequency laser system was used to measure macrotexture. Changes in microtexture, also a factor in skid resistance, were evaluated using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Balmer [36] showed that about (0.02 inch to 0.12 inch) 0.5 to over 3 mm change in surface texture causes a difference of 16 km/h (10 mph) in speed for the initiation of hydroplaning [36] [37].…”
Section: Features Of the Pavement Surfacementioning
confidence: 99%
“…Balmer [36] showed that about (0.02 inch to 0.12 inch) 0.5 to over 3 mm change in surface texture causes a difference of 16 km/h (10 mph) in speed for the initiation of hydroplaning [36] [37].…”
Section: Features Of the Pavement Surfacementioning
confidence: 99%
“…The influence of the mix design method on pavement texture was also investigated [Stroup-Gardiner et al 2004]. The authors compared different mixes (nine Marshall and nine Superpave mix designs) and road sections (located in Alabama) and…”
Section: Proportioningmentioning
confidence: 99%
“…There are still no effective methods to accurately characterize microtexture until now. A number of studies used the British pendulum tester (BPN) to characterize microtexture and evaluate skid resistance at low speeds [9,10]. Liu et al found that the friction coefficient measured by BPN was significantly affected by macrotexture.…”
Section: Introductionmentioning
confidence: 99%